The analysis of pile-pile cap behavior under static loading test using distributed fiber optic sensor - Tanti Muliati; Paulus Pramono Rahardjo; Bondan Widi Anggoro; Ricky Setiawan (Indonesian Geotechnical Journal, 2022)
Pile-Pile cap behavior was investigated in this study through the utilization of fiber optic sensors to continuously transmit information along the bored pile at a reading interval of 40 mm during each cycle of the static loading test. It is important to note that the fiber optic cables were installed on the two sides of the bored pile connected up to the pile cap to monitor the stress distribution beneath the pile cap while fiber optic sensors were installed under the pile cap. The ultimate axial bearing capacity expected to be achieved using the pile-pile cap configuration was 190 tons x 250% but failure occurred when the load used was increased to 190% of the design load. Therefore, the strain measurement obtained from the Distributed Fiber Optic Sensor Technology was analyzed to obtain information on the load transfer, pile shortening, mobilized unit skin friction, and mobilized end bearing at the pile-pile cap. The load portion carried out by pile cap was approximated at 6% to 23% from the actual top load applied. It was also discovered that the fiber optic sensors initially installed were able to record the strain caused to the soil by the load on the pile cap. The strain measurements on the soil made the zone of influence due to the loading of the foundation to reach two times the length of the pile while the biggest zone of influence lies at the end of the foundation. From recorded strain, show higher strain from one side compared to the other, this may indicate eccentricity of the load.